Indications of Hysterectomy for Benign Gynecologic Conditions in a Tertiary Care Hospital - Somjee, Zehra; Seetlani, Pooja; Aslam, Mahrukh; Shaista (Indus Journal of Bioscience Research, 2025)
Objective: To identify the indications and acute complications of hysterectomy performed for benign gynecologic conditions in a tertiary care hospital. Study Design: Descriptive Longitudinal Study. Place and Duration of Study: Department of Obstetrics and Gynecology, Unit 1, Civil Hospital Karachi in the duration from 24 November, 2024 to 23 March, 2025. Methodology: Data was collected from women aged 18–65 years undergoing hysterectomy for benign gynecologic conditions. Demographic details, preoperative diagnoses, intra-operative findings, and post-operative outcomes were analyzed. The primary outcome was the frequency of indications, while secondary outcomes focused on complications. SPSS Version 22 was used for statistical analysis, with a p-value <0.05 considered significant. Results: Common indications included uterine fibroids in 105 cases (53.6%), adenomyosis in 40 (20.4%) patients and uterine prolapse in 30 patients (15%). Complications such as wound infections (14 patients, 7%), hemorrhage (10 patients 5%), and burst abdomen (2 patients, 1%) were observed. Conclusion: Understanding indications and outcomes of hysterectomy can guide better clinical practices and improve patient safety.